Metagenomic Next-Generation Sequencing for Diagnosis of Infectious Encephalitis and Meningitis: A Large, Prospective Case Series of 213 Patients - Xing, Xiao-Wei; Zhang, Jia-Tang; Ma, Yu-Bao; He, Mian-Wang; Yao, Guo-En; Wang, Wei; Qi, Xiao-Kun; Chen, Xiao-Yan; Wu, Lei; Wang, Xiao-Lin; Huang, Yong-Hua; Du, Juan; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Purpose: This study aimed to assess the diagnostic performance of metagenomic next-generation sequencing (mNGS) for prediction of infectious encephalitis and meningitis. Methods: This was a multicenter, prospective study. The cerebrospinal fluid samples collected from patients, who were categorized into viral encephalitis and meningitis, TBM, bacterial meningitis (BM), fungal meningitis and non-infections of CNS, were detected by mNGS. Results: A total 213 patients with infectious and non-infectious CNS diseases were finally enrolled from November 2016 to May 2019, and the positive rate of mNGS for definite CNS infections was 57.0%. When species-specific read number (SSRN) ≥2, the performance of mNGS for the diagnosis of definite viral encephalitis and meningitis was largest (AUC=0.659, 95%CI=0.566-0.751) and the positive rate was 42.6%. When genus-specific reads number ≥1, the performance of mNGS for TBM (definite and probable) was largest (AUC=0.619, 95%CI: 0.516-0.721) and the positive rate was 27.3%. When SSRN ≥5 or 10, the diagnostic performance was the largest (0.846, 95%CI: 0.711-0.981) in definite BM and the sensitivity was 73.3%. The sensitivity of mNGS (SSRN ≥2) in the diagnosis of cryptococcal meningitis and cerebral aspergillosis was 76.92% and 80%, respectively. Conclusion: mNGS of CSF is an effective diagnostic method for identifying the pathogens of infectious CNS diseases. And mNGS should be applied in conjunction with conventional microbiologic testing.